A reflection on the epistemology of fact-checking journalism: challenges and dilemmas - Rodríguez Pérez, Carlos (2020)
Fact-checking journalism has progressed worldwide and has a greater impact on public debate. This article raises a thought focused on the epistemological challenges and dilemmas of fact-checking journalism to achieve the triple objective of this new journalistic genre to be fulfilled: ensure the veracity of the information disseminated on social networks and platforms, address scrutiny of power and transform the information in knowledge assumed by the citizens. Through the analysis of the methodology of Latin American Spanish-speaking fact-checking media, several issues related to the verification, dissemination and reception process are discussed. Likewise, the citizen's role in the fact-checking journalism process is analysed as well as the data dissonance in the two main fact-checking lists (International Fact-Checking Network and the Duke Reporter's Lab).